Enantioselective Electrocatalytic Nitroalkylation - Li, Juan; Song, Jin; Guo, Chang (Synlett, 2025)
Asymmetric electrocatalytic processes hold great promise for the sustainable synthesis of chiral compounds. However, maintaining stereochemical control during the anodic oxidative cross-dehydrogenative coupling of different nucleophiles poses significant challenges. To address this, a novel electrocatalytic strategy has been developed that achieves an enantioconvergent nitroalkylation between benzoxazolyl esters and nitroalkanes via radical pathways. This method produces enantioenriched nitro esters without the need for additional stoichiometric chemical oxidants. Mechanistic studies have revealed that the nickel catalyst plays a critical role in both the electrochemical activation and the determination of stereoselectivity. This approach facilitates transformations that are challenging under thermal conditions, including umpolung reactivity, the formation of quaternary carbon centers, and remote enantiocontrol.
Keywords: electrocatalysis; radical reaction; nickel catalysis; enantioselectivity; cross-dehydrogenative coupling; nitroalkylation